Synchronizing Web Documents with Style - Guimarães, Rodrigo Laiola; Bulterman, Dick; Cesar, Pablo; Jansen, Jack (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
In this paper we report on our efforts to define a set of document extensions to Cascading Style Sheets (CSS) that allow for structured timing and synchronization of elements within a Web page. Our work considers the scenario in which the temporal structure can be decoupled from the content of the Web page in a similar way that CSS does with the layout, colors and fonts. Based on the SMIL (Synchronized Multimedia Integration Language) temporal model we propose CSS document extensions and discuss the design and implementation of a proof of concept that realizes our contributions. As HTML5 seems to move away from technologies like Flash and XML (eXtensible Markup Language), we believe our approach provides a flexible declarative solution to specify rich media experiences that is more aligned with current Web practices.